Células tronco mesenquimais da medula óssea de ratas Wistar idosas não diminuem o potencial de diferenciação condrogênico sob efeito da triiodotironina - Silva, Isabella Cosmo da (2019)
The potential for bone marrow mesenchymal stem cell differentiation (CTM-MO) decreases in humans and older Sprague Dawley rats. In addition, triiodothyronine (T3) treatment improves the chondrogenic potential in CTM-MO of young Wistar rats. Thus, the aim of this study was to evaluate the potential for chondrogenic differentiation of CTM-MO from older Wistar rats and the influence of T3. For this purpose, aseptic CTM MO was collected from six old Wistar rats (12 months old) and six young Wistar rats (one month old). The cells were cultured in vitro in basic culture medium and distributed in the following groups: 1) CTM-MO young rats without T3 treatment; 2) CTM-MO of elderly rats without T3 treatment; 3) CTM-MO of aged rats treated with 0.01 nM T3; 4) CTM-MO of 1000 nM T3 treated elderly rats. After seven, 14 and 21 days of differentiation, the expression of Sox-9, agrecane (Agg) and collagen II (Col II), cell morphology and chondrogenic matrix formation were evaluated. Analysis of variance (ANOVA) was performed followed by statistical tests according to the sample data. The expression of Sox9 and Agg was higher in group (2) compared to group (1) periodically. However, glycosaminoglycan formation was similar between these groups. The use of 0.01 and 1000 nM T3 reduced Agg expression in a period dependent manner, but did not alter Sox9 and Col II expression and glycosaminoglycan formation. It was concluded that at 12 months of age, Wistar rats provide good cell source and hormonal treatment is not necessary, since the potential of chondrogenic differentiation of CTM-MO from elderly rats without T3 treatment is not changed with chronological age